Late Weichselian and Holocene palaeoceanography of Storfjordrenna, southern Svalbard - Łącka, Magdalena; Zajączkowski, Marek; Forwick, Matthias; Szczuciński, Witold (My University, 2015)
Multiproxy analyses (including benthic and planktonic foraminifera, δ18O and δ13C records, grain-size distribution, ice-rafted debris, XRF geochemistry and magnetic susceptibility) were performed on a 14C-dated marine sediment core from Storfjordrenna, located off of southern Svalbard. The sediments in the core cover the termination of Bølling–Allerød, the Younger Dryas and the Holocene and reflect general changes in the oceanography/climate of the European Arctic after the last glaciation. Grounded ice of the last Svalbard–Barents Sea Ice Sheet retreated from the coring site ca. 13 950 cal yr BP. During the transition from the subglacial to glaciomarine setting, Arctic Waters dominated the hydrography in Storfjordrenna. However, the waters were not uniformly cold and experienced several warmer spells. A progressive warming and marked change in the nature of the hydrology occurred during the early Holocene. Relatively warm and saline Atlantic Water began to dominate the hydrography starting from approximately 9600 cal yr BP. Although the climate in eastern Svalbard was milder at that time than at present (smaller glaciers), two periods of slight cooling were observed in 9000–8000 and 6000–5500 cal yr BP. A change in the Storfjordrenna oceanography occurred at the beginning of the late Holocene (i.e. 3600 cal yr BP) synchronously with glacier growth on land and enhanced bottom current velocities. Although cooling was observed in the Surface Water, Atlantic Water remained present in the deeper portion of the water column of Storfjordrenna.
Keywords: Svalbard; Holocene; Paleoceanography